FENOMENA DINASTI POLITIK: Studi Kasus Dewanti Rumpoko Sebagai Wali Kota Batu Tahun 2017 - Gracelin (2023)
This study aims to find out how Dewanti's power is managed in maintaining Rumpoko's power with the support of Eddy Rumpoko's role as local bossism so that a political dynasty is formed in Batu City in 2017. The method used in this research is qualitative. The type of research used is explanation with a case study approach using primary and secondary data sources. Researchers used three stages of data analysis according to Sugiyono (2013), namely; data reduction, data presentation and conclusions as well as verification. To support this, this explanatory research uses in-depth interviews and collects documents to obtain data. This study uses the main theories, namely the theory of oligarchy by Jeffrey Winters and the concept of local bossism by John T. Sidel. The results of this study are that the election of Dewanti Rumpoko as Mayor of Batu City in 2017 is a form of perpetuating oligarchic power in Batu City with the help of local bossism, namely Eddy Rumpoko as husband and Paul Sastro in the world of politics and business. Dewanti Rumpoko's victory did not escape the help of Eddy Rumpoko who carried out money politics in various sub-districts in Batu City, and financial assistance from Paul Sastro, resulting in a patron-client relationship between Eddy Rumpoko and Paul Sastro, namely Paul Sastro who would help Eddy Rumpoko finance and Eddy Rumpoko who will help Paul Sastro in his business in Batu City. From this statement the oligarchic structure that occurred in Batu City leads to a political dynasty. The impact of this political dynasty is the changing spatial planning and land conversion of Batu City, as well as social inequality.